2017
DOI: 10.3389/fnhum.2017.00581
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neural Activity during Guided Viewing of Visual Art

Abstract: Mobile Brain-Body Imaging (MoBI) technology was deployed to record multi-modal data from 209 participants to examine the brain’s response to artistic stimuli at the Museo de Arte Contemporáneo (MARCO) in Monterrey, México. EEG signals were recorded as the subjects walked through the exhibit in guided groups of 6–8 people. Moreover, guided groups were either provided with an explanation of each art piece (Guided-E), or given no explanation (Guided-NE). The study was performed using portable Muse (InteraXon, Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…There is rapidly growing interest in studying cognition and perception in the context of naturalistic settings, such as classrooms ( Dikker et al, 2017 ), movie theaters ( Fröber and Thomaschke, 2019 ), art museums ( Brieber et al, 2014 ; Herrera-Arcos et al, 2017 ), and live theaters ( Ardizzi et al, 2020 ). Despite this current trend, studies investigating listener responses to music in live concert settings are still relatively uncommon, perhaps due to the logistical challenges and relative lack of experimental control when conducting such work.…”
Section: Introductionmentioning
confidence: 99%
“…There is rapidly growing interest in studying cognition and perception in the context of naturalistic settings, such as classrooms ( Dikker et al, 2017 ), movie theaters ( Fröber and Thomaschke, 2019 ), art museums ( Brieber et al, 2014 ; Herrera-Arcos et al, 2017 ), and live theaters ( Ardizzi et al, 2020 ). Despite this current trend, studies investigating listener responses to music in live concert settings are still relatively uncommon, perhaps due to the logistical challenges and relative lack of experimental control when conducting such work.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon highlights the spatial factors that also affect the UX in aesthetic appreciation, affective processing, and usability testing. The research of Herrera-Arcos et al observed people in a museum to find that beta-band suppression is present during engagement and aesthetic appreciation towards their favorite paintings [ 31 ]. Moreover, past research on UX focused on delay and subjectively experienced time.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies of cognitive functions include research of relevance judgement (Emotiv) [54], decision making (Emotiv) [61], mental workload (NeuroSky) [55], mental fatigue and stress (NeuroSky, Muse, and Emotiv) [56,57,63], subconscious face recognition (Emotiv) [53], and esthetic preference (Muse) [58].…”
Section: Study Of Cognitionmentioning
confidence: 99%
“…Further research in the field of cognition study investigated the possibility to investigate the subconscious mind via facial recognition [53] and to identify the individual's artistic preference [58]. The first work used the Emotiv EPOC headset for collecting signals during seeing of well-known people and SVM classifiers to analyze the data.…”
Section: Study Of Cognitionmentioning
confidence: 99%